Predefined Time Anti-Unwinding Control of Rigid Spacecraft Attitude Tracking - Liangmou Hu; Zeng Wang; Hanghang Wang; Changrui Chen; Heng Yue; Jiale Wang (IEEE Access)
This paper addresses the predefined time anti-unwinding attitude tracking control of rigid spacecraft with inertial uncertainties and external disturbances. Firstly, a new predefined-time terminal sliding surface (FTS) is proposed with hybrid technique. Secondly, a simple predefined-time sliding mode control (PTAC) is exploited to solve the robust attitude tracking problem. It is proved that the proposed PTAC can ensure that the attitude tracking errors tend to an arbitrary small bound centered on equilibrium point within predefined time and then go to equilibrium point asymptotically. The features of the PTAC includes robust, anti-unwinding and predefined time. To verify the effectiveness of the developed scheme, the numerical simulations are demonstrated.